The Sound of a Room: Memory and Auditory Presence of Place - Köseoğlu, Emine (Routledge, 2025)
Seán Street’s The Sound of a Room: Memory and Auditory Presence of Place (2020) is an original work that invites the reader to reconsider space – often regarded as a purely physical entity – as a field of auditory experience. By treating sound, which is invisible and therefore prone to neglect, as a significant dimension, the book calls on the reader to forge a different connection with both their surroundings and their own past through deep listening. Street’s text is not woven with academic jargon, yet it provides a sensory ground that can naturally accompany spatial experience through its intuitive strength, narrative power, and poetic depth.